Anti-war and anti-draft protest - Spartan Daily:::Creator::::::::::::
Anti-war and anti-draft student protest. Two students are seated, while another person is talking. The female student has her arms folded across her chest, while a male student is reading from a document. Posters announcing a student strike for peace event are situated between the seated student. A large peace symbol is prominent on the poster on the left, and to the right, a mock oversized poster reads: Selective Service System Certificate;Resist April 29, 1968 written across the certificate.